Pengembangan Perangkat Pembelajaran Model Blender (Blended Learning) untuk Membangun Pemahaman Materi Fungsi - Nur Rohman; Junarti Junarti; Ari Yoga Pangestu (LPPM Press, 2022)
Abstract: This research is a research that develops mathematics learning tools using a model Blended Learning (BLENDER) on the material limit of algebraic functions. The background of this research is that mathematics learning tends to use the lecture method and students are not yet actively involved in the learning process, In addition, in the process of calculating the limit value, students still have difficulty. This study aims to develop mathematics learning tools, describe the quality of model learning tools Blended Learning and knowing the students' responses to the mathematics learning process on the material limit of algebraic functions. This study uses a model ADDIE which includes: (1) the analysis phase (Analysis), (2) the design phase, (3) the development phase, (4) the implementation phase, and (5) the evaluation phase. The learning tools developed are the syllabus and lesson plans. The subjects of this study were students of class XII TEI SMK Negeri 2 Bojonegoro. The object of research is all the learning tools developed by the researcher. The learning tools developed are the syllabus and lesson plans. The subjects of this study were students of class XII TEI SMK Negeri 2 Bojonegoro. The object of research is all learning tools developed by researchers. Data collection techniques used are observation and interviews. The results of the study show that: 1) Learning tools have been successfully developed using the ADDIE model, 2) The results of the validation of learning devices are 4 including good categories. The results of student completeness reached 91.4% in the very good category, 3) The results of the questionnaire student responses to the learning process using the Blended Learning model obtained 82.9% results included in the good category. Teachers find it helpful in carrying out learning by using the Blended Learning model. Keywords: BLENDER learning tools; Blended Learning models; Limits of Algebraic Functions